Vietnam: constitutions as signalling instruments - Nicholson, Pip (Đại học Quốc Gia Hà Nội, 2020)
This paper sits at the intersection of two sites of constitutional scholarship. First, it draws on Ginsberg and Simpser’s significant work on authoritarian constitutions which reflects on:i. What do authoritarian constitutions do?ii. How do they work?iii. Why do they exist?1 - At least part of the answer to these three questions offered by Ginsberg and Simpser lies in their characterisation of the signalling power of constitutions, and we turn to that shortly.2- Secondly, during a discussion at a 2016 National University of Singapore conference, a group of scholars argued, at least in part, that the Vietnamese constitution of 2013 was not specific in certain critical respects. If we accept this insight, what implications does that have for constitutional signalling in socialist states?Today, we suggest that the 2013 Vietnamese Constitution has signalling power, while also containing not very specific provisions. This in combination with the political role of socialist constitutions, confirms that signalling can be significant, but also that it can be dynamic and what is signalled can fluctuate. Actors involved in negotiating the signals include the Party-state and reformers. Signals leave an elastic space, and where ambiguities exist; these can operate regressively or progressively.